Drowning Associated Diatoms (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Drowning is type of asphyxial death by submersion in a fluid, whether or not the fluid is aspirated into the lungs. This is considered  as the cause of death if the death occurs within 24 hours of the insult and if survival is beyond 24 hours after the submersion and  implies that recovery has occurred after the insult it is called near drowning.  Diatoms are among the well known water planktons. Every water body has its own diatom diversity. Diatoms are autotrophic in  nature and different genera are found in both marine and fresh habitats. Diatoms belong to class Bacillariophyceae and further divided into two orders i.e. Centrals and Pennales on the basis of their symmetry. There are about 10,000 species and 174  genera of diatoms having different shapes and sizes ranging from 1 to 500µm. Diatoms are commonly found in water bodies like  ponds, lakes, canals and rivers etc. but their concentration can be low or high in a particular water body, depending upon the  season. With regard to another feature-the water depth limits to benthic distribution-there is no incontrovertible evidence for autotrophic growth of diatoms below about 100 m.
Keywords: planktons; Drowning; Bacillariophyceae